2022
DOI: 10.1111/andr.13291
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis is involved in corpus cavernosum smooth muscle cells impairment in diabetes mellitus‐induced erectile dysfunction

Abstract: Backgrounds: Erectile dysfunction (ED) is a common andrological disorder that tends to afflict diabetic patients, among others. Pharmacological therapy of diabetes mellitus-induced ED (DMED) is ineffective, as it is linked with smooth muscle cell loss in the corpus cavernosum. Ferroptosis is a recently identified kind of cell death evoked by lipid peroxidation, and it is connected with a number of diabetic complications.Objectives: To investigate the role of ferroptosis in DMED. Materials and methods:We establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Recent studies have demonstrated that ferroptosis is related to the OS of CCSMCs in diabetes mellitus-induced ED and that human umbilical cord mesenchymal stem cells could treat diabetes mellitus-induced ED by inhibiting OS via attenuation of ferroptosis [ 36 , 37 ]. Similarly, we were surprised to find that the total iron ( Figure 6(e) ) and MDA ( Figure 6(f) ) contents in the PBS group were significantly higher than those in the sham group ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that ferroptosis is related to the OS of CCSMCs in diabetes mellitus-induced ED and that human umbilical cord mesenchymal stem cells could treat diabetes mellitus-induced ED by inhibiting OS via attenuation of ferroptosis [ 36 , 37 ]. Similarly, we were surprised to find that the total iron ( Figure 6(e) ) and MDA ( Figure 6(f) ) contents in the PBS group were significantly higher than those in the sham group ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…39 And ferroptosis strengthened the connectivity relevance to oxidative stress, inflammation, and cardiovascular diseases. 36 Similarly, Xu et al 40,41 reported that ferroptosis was responsible for the corpus cavernosum smooth muscle cells impairment in DMED, and GPX4 was feasible for the treatment of DMED via inhibiting ferroptosis. Besides, autophagy was noticed in the process of DMED, and autophagosomes, as well as…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] In addition, comprehensive analysis methods such as microarrays and RNA sequencing (RNA-seq) have been developed, making it possible to evaluate factors that have not been studied in the past, leading to rapid progress in research. 28,29 Western blotting has also been used to measure protein expression levels, and significant progress has been made with the development of enzyme-linked immunosorbent assay (ELISA) kits and quantification methods using liquid chromatography-mass spectrometry (LC-MS) to measure protein levels. [30][31][32] In basic research on sexual function, the animal species used are changing along with the development of research methods.…”
Section: E Xperimental Techni Que S and Animal S Pecie S For Re S E A...mentioning
confidence: 99%